The Effectiveness of Educational Tools Grounded in Local Knowledge in Enhancing High School Students' Creative Thinking Skills in the Context of Sound Waves - Trisnawaty Junus Buhungo; Mursalin Mursalin; Reka Lagani (JIPF (Jurnal Ilmu Pendidikan Fisika), 2023)
The objective of this study was to describe the effectiveness of learning tools based on local wisdom in enhancing creative thinking skills in the context of sound waves. The research was conducted at SMA N 1 North Gorontalo, specifically targeting eleventh-grade students. The study employed a Research and Development (R&D) approach, utilizing the ADDIE learning design model, which encompasses the stages of Analysis, Design, Development, Implementation, and Evaluation. However, it is important to note that this study focuses solely on describing the effectiveness of the learning materials, without delving into other aspects. The effectiveness of the learning tools was assessed during the implementation stage. The findings of the study indicated that student engagement during the two sessions was rated as very good. The assessment of attitudes in both sessions resulted in a percentage of 87.89% and 89.85% respectively, falling within the very good category. Similarly, the assessment of skills exhibited percentages of 85.70% and 89.85% respectively, also within the very good range. Furthermore, the test conducted to evaluate students' creative thinking abilities revealed that the majority of students demonstrated creativity in utilizing traditional polopalo musical instruments. These findings suggest that learning tools based on local wisdom have the potential to enhance students' creative thinking skills.